Silicon based unified memory devices and technology - Bhattacharyya, Arup (Boca Raton, FL : CRC Press, 2017)
"The primary focus of this book is on basic device concepts, memory cell design, and process technology integration. The first part provides in-depth coverage of conventional nonvolatile memory devices, stack structures from device physics, historical perspectives, and identifies limitations of conventional devices. The second part reviews advances made in reducing and/or eliminating existing limitations of NVM device parameters from the standpoint of device scalability, application extendibility, and reliability. The final part proposes multiple options of silicon based unified (nonvolatile) memory cell concepts and stack designs (SUMs). The book provides Industrial R & D personnel with the knowledge to drive the future memory technology with the established silicon FET-based establishments of their own. It explores application potentials of memory in areas such as robotics, avionics, health-industry, space vehicles, space sciences, bio-imaging, genetics etc."--Provided by publisher.
3.5.1 Bulk-Controlled Poole-Frenfel Mechanism3.5.2 Electrode-Controlled Quantum Mechanical Tunneling Mechanisms; 3.5.3 Direct Tunneling and/or Modified Fowler-Nordheim Tunneling; 3.5.3.1 Fowler-Nordheim Tunneling; 3.5.3.2 Enhanced Fowler-Nordheim Tunneling; 3.6 Carrier Transport Mechanisms for Multilayer Dielectrics; References; Chapter 4 Dielectric Films for NVM Devices; 4.0 Conventional Dielectric Films for NVM Devices; 4.1 Thermal Oxide: SiO2; 4.1.1 Defect Generation and Oxide Degradation; 4.1.1.1 Oxide Reliability; 4.2 CVD or LPCVD Nitride: Si3N4.
4.2.1 Nitride Traps, Trap Creation: Process and Stress Sensitivity.
OCLC-licensed vendor bibliographic record.
Keywords: Semiconductor storage devices -- Design and construction; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- General; TECHNOLOGY & ENGINEERING -- Electronics -- Microelectronics; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General; TECHNOLOGY / Electronics / Circuits / General